Imagery in Scientific Discourse - Natalya Yu. Kozlova (RUDN Journal of Philosophy, 2023)
The article is an overview of the problems on the topic of figurativeness in scientific discourse. The analysis was carried out in three perspectives: “conceptual” - the key ideas about the role of figurativeness in the formation of scientific discourse (about metaphorical schemes that lie in the processes of thinking and scientific conceptualization, about the need to identify and analyze these schemes in science, about the role of comparison and analogy in the conceptual and semantic deployment of scientific discourse); “narrative” - the ideas about the function of figurativeness in the development of the author’s ontology are considered (the problems of constructing a rhetorical “Self” in scientific discourse, “self-identifying narrative”, “scientific identity”); “communicative” - the specificity of figurativeness is revealed in connection with the problem of knowledge transfer and modern strategies for popularizing science. It is shown that in the context of the modern identification of the “rhetoric” of scientific communication and discussion of strategies for science popularizing, the research topic is characterized by particular relevance. The analysis of figurativeness in scientific discourse touches upon the problem of the dialogue between science and society, which is important for our time, and how scientific achievements fit into socio-cultural and educational contexts. It is shown that the scientific significance of the study of figurativeness in scientific discourse is manifested in the fact that it allows, firstly, to expand the concept of “scientific”, revising the ideals of academic scientificity, often translating a view of science as an “emotionally emasculated” “substrate” of objective and transparent truth, and thereby overcome the existing communicative “barrier” between society and the scientific community; secondly, to rethink ideas about the communicative specifics of scientific creativity and the role of language in constructing the semantic and logical-methodological space of science.